Polyetherimide / polyurethane fiber sponge as well as preparation method and application thereof
By filling polyurethane nanofibers in the polyetherimide microfiber framework to form a three-dimensional crosslinking network structure of polyetherimide/polyurethane fiber sponge, the existing fiber sponge has solved the problems of poor resilience and poor thermal insulation performance, and achieved high-performance flame retardant insulation and soft rebound characteristics, which are suitable for a variety of application fields.
Patent Information
- Application Number
- CN202510405534.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-02
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-04-02
AI Technical Summary
The existing polyetherimide fibers have poor resilience and poor thermal insulation performance, which cannot meet the application needs in the field of flexible thermal insulation and flame retardant.
Polyetherimide/polyurethane fiber sponge with a three-dimensional crosslinking network structure is formed by filling the polyurethane nanofibers in the polyetherimide microfiber skeleton. The method includes dissolving polyetherimide and polyurethane in an organic solvent, adding a crosslinking agent and preparing a fiber sponge through a multi-nozzle blending electrospinning process.
It improves the elasticity and thermal insulation properties of fiber sponge, making it have excellent flame retardant insulation and soft rebound characteristics, and is suitable for clothing, building insulation and protective wear.
Smart Images

Figure CN119900107A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer material preparation, and in particular to a polyetherimide / polyurethane fiber sponge and a preparation method and application thereof. Background Art
[0002] Polyetherimide is an amorphous polymer containing an imide ring and an ether bond in its molecular structure. It does not soften or shrink at high temperatures, has stable thermal insulation properties, and has excellent intrinsic flame retardancy. It can still maintain its shape and good flame retardancy above 200°C, meeting the fire protection requirements in high temperature environments. The toxicity of the smoke and toxic gases released when it burns is significantly lower than that of common materials such as PVC and ABS. It is an excellent flame retardant and thermal insulation material. However, it is highly brittle, difficult to mold and process, and lacks the flexibility of porous materials, which limits its application in the field of flexible thermal insulation and flame retardancy, and cannot meet some scenarios with high requirements for material flexibility. Therefore, it is necessary to develop materials with excellent comprehensive performance to improve its application in the field of flexible thermal insulation and flame retardancy.
[0003] To solve this problem, existing patents usually compound it with other materials to improve its performance. For example, the prior art with application publication number CN103361832A discloses a blended fabric of polyetherimide and flame retardant viscose. The flame retardant viscose fiber is prepared by a wet spinning process of a flame retardant and a viscose solution. The fabric has good flame retardant properties.
[0004] However, the blended fabric has the following problems: (1) The fabric needs to be synthesized first by synthesizing flame-retardant viscose fiber and then blended with polyetherimide fiber. The preparation process involves multiple complex steps and the production cost is high. (2) The wet spinning solution is difficult to recycle and the loss rate is high. (3) There is no strong interface bonding between the two fibers and the thermal insulation performance is poor. (4) Additional flame retardant loading is required, which is not in line with the trend of green chemistry. (5) The fabric has low elasticity and can only be used as a surface covering material, and cannot be used in the thermal insulation interlayer of protective wearable materials. Summary of the invention
[0005] The present application discloses a polyetherimide / polyurethane fiber sponge and a preparation method and application thereof, aiming to solve the technical problems of poor resilience and poor thermal insulation performance of the existing polyetherimide fibers.
[0006] In order to achieve the above purpose, the technical solution of this application is:
[0007] The first aspect of the present application provides a polyetherimide / polyurethane fiber sponge, comprising: polyetherimide micron fibers and polyurethane nanofibers;
[0008] The polyurethane nanofibers are filled in a polyetherimide micron fiber skeleton to form a polyetherimide / polyurethane fiber sponge with a three-dimensional cross-linked network structure.
[0009] In combination with the first aspect, preferably, the diameter of the polyetherimide micron fiber is 1-3 μm.
[0010] In combination with the first aspect, preferably, the diameter of the polyurethane nanofiber is 100-500 nm.
[0011] The second aspect of the present application provides a method for preparing the polyetherimide / polyurethane fiber sponge described in the first aspect, the preparation method comprising:
[0012] Dissolving polyetherimide in a first organic solvent, adding a cross-linking agent, and obtaining a polyetherimide spinning solution;
[0013] dissolving the polyurethane in a second organic solvent to obtain a polyurethane spinning solution;
[0014] The polyetherimide spinning solution and the polyurethane spinning solution are subjected to a multi-nozzle blending electrostatic spinning process, and then subjected to a heat treatment to obtain the polyetherimide / polyurethane fiber sponge;
[0015] Wherein, the first organic solvent and the second organic solvent are the same or different.
[0016] In combination with the second aspect, preferably, the cross-linking agent is one of aziridine, bismaleimide and genipin.
[0017] In combination with the second aspect, preferably, the solid content of the polyetherimide spinning solution is 18%-26%;
[0018] The solid content of the polyurethane spinning solution is 18%-24%;
[0019] The volume ratio of the polyetherimide spinning solution to the polyurethane spinning solution is (1-3):1.
[0020] In combination with the second aspect, preferably, the added amount of the cross-linking agent is 1.5%-3% of the mass of the polyetherimide.
[0021] In combination with the second aspect, preferably, the first organic solvent is one or more of N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone;
[0022] The second organic solvent is one or more of N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone.
[0023] In combination with the second aspect, preferably, the parameters of the multi-nozzle blending electrospinning process are: spinning voltage: 20-30kV; spinning temperature: 25-35 ℃; spinning humidity: 40%-65%; spinning time: 3-8 h; syringe advancement speed: 0.05-0.2mm / min; syringe left and right translation: 40-120 mm; roller receiving speed: 20-50 r / min; receiving distance: 15-30 cm.
[0024] The third aspect of the present application provides the use of the polyetherimide / polyurethane fiber sponge described in the first aspect or the polyetherimide / polyurethane fiber sponge prepared by the preparation method described in the second aspect in the fields of clothing, building insulation, and protective wear.
[0025] Compared with the prior art, the advantages or beneficial effects of the embodiments of the present application include at least:
[0026] The polyetherimide / polyurethane fiber sponge provided by the present application forms a three-dimensional cross-linked network structure by filling polyurethane nanofibers in a polyetherimide micron fiber skeleton. On the one hand, the polyetherimide micron fiber provides a solid skeleton support for the fiber sponge, and the polyurethane nanofibers are filled in the polyetherimide micron fiber skeleton, and the fiberization enhances the interfacial bonding force and the synergistic effect of the cross-linking agent, so that the fiber sponge maintains stable physical and chemical properties at higher temperatures; on the other hand, the polyurethane nanofibers are doped in the skeleton of the polyetherimide micron fiber, which reduces the internal voids of the fiber sponge, greatly improves the thermal insulation performance, and makes the fiber sponge have excellent flame retardant, thermal insulation and soft rebound properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0028] Figure 1 A physical picture of the A1-polyetherimide / polyurethane fiber sponge provided in the examples of the present application;
[0029] Figure 2 This is a SEM image of the A1-polyetherimide / polyurethane fiber sponge provided in the examples of the present application;
[0030] Figure 3 This is a combustion test diagram of A1-polyetherimide / polyurethane fiber sponge provided in the examples of the present application;
[0031] Figure 4This is a thermal insulation test diagram of the A1-polyetherimide / polyurethane fiber sponge provided in the examples of the present application. DETAILED DESCRIPTION
[0032] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0033] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.
[0034] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0035] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0036] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0037] It should be noted that all raw materials and reagents in the examples of the present application were purchased on the market or prepared according to conventional methods well known to those skilled in the art.
[0038] In a first aspect, an embodiment of the present application provides a polyetherimide / polyurethane fiber sponge, comprising: polyetherimide micron fibers and polyurethane nanofibers;
[0039] The polyurethane nanofibers are filled in a polyetherimide micron fiber skeleton to form a polyetherimide / polyurethane fiber sponge with a three-dimensional cross-linked network structure.
[0040] Among them, on the one hand, polyetherimide micron fiber provides a solid skeleton support for the fiber sponge, and polyurethane nanofibers are filled in the polyetherimide micron fiber skeleton. Through fiberization, the interfacial bonding force is enhanced and the synergistic effect of the cross-linking agent is achieved, so that the physical and chemical properties are kept stable at higher temperatures. On the other hand, polyurethane nanofibers are doped in the skeleton of polyetherimide micron fibers, which reduces the internal voids of the fiber sponge and greatly improves the thermal insulation performance, making the fiber sponge have excellent flame retardant, thermal insulation and soft rebound properties.
[0041] In the embodiment of the present application, the diameter of the polyetherimide micron fiber is 1-3 μm. The diameter of the polyurethane nanofiber is 100-500 nm. Among them, the polyetherimide micron fiber acts as the skeleton of the three-dimensional fiber sponge, and the fiber diameter should be appropriate. If the fiber diameter is large, the rigidity of the skeleton will be stronger, and the internal space of the sponge will be larger. After the polyurethane nanofiber is filled, a large amount of space will still remain, which is not conducive to the improvement of thermal insulation performance. If the fiber diameter is small, the thinner fibers cannot form a sponge skeleton. The polyurethane nanofiber can be entangled with the polyetherimide micron fiber, and can play a role similar to a "reinforcer" in the blended system, filling in the gaps between the micron fibers to increase the friction and cohesion between the fibers. At the same time, the addition of a cross-linking agent can further connect the fibers to form a more stable mesh structure, and the synergistic effect of the two can significantly improve the mechanical properties of the fiber sponge.
[0042] The second aspect of the present application provides a method for preparing the polyetherimide / polyurethane fiber sponge described in the first aspect, the preparation method comprising:
[0043] Dissolving polyetherimide in a first organic solvent, adding a cross-linking agent, and obtaining a polyetherimide spinning solution;
[0044] dissolving the polyurethane in a second organic solvent to obtain a polyurethane spinning solution;
[0045] The polyetherimide spinning solution and the polyurethane spinning solution are subjected to a multi-nozzle blending electrostatic spinning process, and then subjected to a heat treatment to obtain the polyetherimide / polyurethane fiber sponge;
[0046] Wherein, the first organic solvent and the second organic solvent are the same or different.
[0047] It should be noted that the present application uses electrostatic spinning and multi-nozzle hand-blending technology to form a cross-linked complementary structure between polyetherimide and polyurethane at the micron / nanoscale, so that the fiber sponge has thermal insulation performance and good elasticity. At the same time, it can also adjust the spinning parameters to obtain a variety of fiber sponges to meet different needs. The preparation method is easy to operate, greatly simplifies the production process, and reduces production costs. By doping polyurethane nanofibers into polyetherimide fibers, the stability of the polyetherimide fiber skeleton is enhanced, which not only maintains excellent flame retardant and thermal insulation properties, but also enhances the resilience of the fiber sponge.
[0048] It should be noted that the polyetherimide used in the present application includes copolymeric polyetherimide and homopolymeric polyetherimide, which can be purchased on the market or prepared according to conventional methods well known to those skilled in the art. Homopolymeric polyetherimide is formed by condensation polymerization of a single diamine and a single dianhydride, and the diamine can be selected from one of 3,5-diaminobenzoic acid, metaphenylenediamine, 3,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl ether, p-phenylenediamine, 4,4'-diaminodiphenylmethane and 4,4'-diamino-2,2'-bistrifluoromethylbiphenyl, and the dianhydride can be selected from one of bisphenol A diether dianhydride, 3,3,4,4-triphenyl diether tetraacid dianhydride, and the like; the copolymeric polyetherimide is formed by condensation polymerization of the following diamines and dianhydrides, and the diamine can be selected from one of 3,5-diaminobenzoic acid, metaphenylenediamine, 3,4'-diaminodiphenylmethane, p-phenylenediamine, One or more of 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane, 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl; the dianhydride is a mixture of diether anhydride and dibasic anhydride, wherein the molar percentage of the diether anhydride is between 90-100% of the mixed anhydride, and the molar percentage of the dibasic anhydride is between 0.1-10% of the mixed anhydride; the diether anhydride can be selected from one or more of bisphenol A diether dianhydride and 3,3,4,4-triphenyl diether tetracarboxylic dianhydride; the dicarboxylic anhydride can be selected from one or more of biphenyl tetracarboxylic dianhydride, pyromellitic dianhydride, benzophenone tetracarboxylic dianhydride, diphenyl ether tetracarboxylic dianhydride, and hexafluoro dianhydride.
[0049] It should be noted that the polyurethane used in the present application is formed by addition polymerization of the following isocyanates and polyols, the isocyanate can be one or more of toluene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate and polymethylene polyphenyl isocyanate, and the polyol can be one or more of polyether polyols, polyester polyols and bio-based polyols.
[0050] In the embodiment of the present application, the crosslinking agent is preferably one of aziridine, bismaleimide and genipin. These crosslinking agents can react with the active groups on the polyetherimide or polyurethane molecules to form covalent bonds, making the bonding between the fibers more firm, thereby enhancing the overall structural stability and mechanical properties of the fiber sponge, and improving its strength and toughness.
[0051] In the embodiment of the present application, the solid content of the polyetherimide spinning solution is preferably 18%-26%, and in order to make the ejected polyetherimide fiber nanofiber, it is more preferably 24%; the solid content of the polyurethane spinning solution is preferably 18%-24%, and more preferably 20%. If the solid content of the spinning solution is too low, the obtained fiber diameter will be uneven and the strength will be low. However, if the content of the spinning solution is too high, problems such as difficulty in solvent volatilization and jet instability may occur, so the concentration of the spinning solution must be appropriate. The volume ratio of the polyetherimide spinning solution to the polyurethane spinning solution is preferably (1-3): 1, and more preferably 3: 1. Polyurethane does not have flame retardant properties. If the added polyurethane content is too high, the flame retardant properties of the fiber sponge will be greatly reduced. However, if the amount of polyetherimide added is too high, the gaps between the formed skeleton structures will increase, and the polyurethane nanofibers cannot effectively fill these gaps, resulting in a decrease in the thermal insulation performance and elasticity of the fiber sponge.
[0052] In the embodiment of the present application, the amount of the cross-linking agent added is 1.5%-3% of the mass of the polyetherimide, and more preferably 2%. Among them, if the amount of cross-linking agent is too small, the degree of cross-linking between the fibers is insufficient, the mechanical properties of the fiber sponge are poor, and relative slippage or breakage between the fibers is likely to occur when subjected to force; and excessive amount of cross-linking agent may cause excessive cross-linking of the fibers, making the fiber sponge hard and brittle, and reducing flexibility and elasticity. Therefore, by precisely controlling the amount of cross-linking agent, a denser network can be formed between the fibers, reducing the pores inside the sponge, while improving the thermal insulation performance, and effectively enhancing the flexibility of the fiber sponge.
[0053] In the embodiment of the present application, the first organic solvent is preferably one or more of N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone; the second organic solvent is preferably one or more of N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone. Among them, by controlling the added solvent, the polymer can be fully dissolved to obtain a uniform and stable spinning solution, ensuring that continuous and uniform fibers are produced during the electrospinning process.
[0054] In the embodiment of the present application, the parameters of the multi-nozzle electrospinning process are preferably: spinning voltage: 20-30 kV, more preferably 25 kV; spinning temperature: 25-35 ° C, more preferably 25 ° C; spinning humidity: 40%-65%, more preferably 55%; spinning time: 3-8 h, more preferably 6 h; syringe propulsion speed: 0.05-0.2 mm / min, more preferably 0.1 mm / min; syringe left and right translation: 40-120 mm, more preferably 80 mm; roller receiving speed: 20-50 r / min, more preferably 25 r / min; receiving distance: 15-30 cm, more preferably 20 cm. Among them, by controlling the ambient temperature of the multi-nozzle electrospinning process, as well as the spinning parameters such as humidity and voltage, the two spinning solutions are electrospun simultaneously to form a uniform composite fiber network, which can give full play to the performance advantages of the two materials. At the same time, the left and right translation of the syringe needs to be greater than the maximum distance between the syringes, otherwise the obtained fiber sponge will have an area where the polyetherimide fiber and the polyurethane fiber are mixed unevenly. Polyetherimide provides high temperature resistance and flame retardancy, while polyurethane imparts flexibility and elasticity. The two form a cross-linked complementary structure at the nano / micrometer scale, which enables the fiber sponge to have flame retardant and heat-insulating properties while also having good elasticity.
[0055] The third aspect of the present application provides the application of the polyetherimide / polyurethane fiber sponge described in the first aspect or the polyetherimide / polyurethane fiber sponge prepared by the preparation method described in the second aspect in the fields of clothing, building insulation, and protective wear. Among them, based on the comprehensive properties of the above-mentioned polyetherimide / polyurethane fiber sponge such as excellent fiber skeleton stability, flame retardancy, thermal insulation, and high elasticity, it has broad application prospects in the fields of clothing, building insulation, and protective wear, and has strong product competitiveness.
[0056] The technical solution of the present application will be further described below in conjunction with specific embodiments.
[0057] Example 1
[0058] This embodiment provides a method for preparing A1-polyetherimide / polyurethane fiber sponge, which specifically includes:
[0059] S101: 11.4 g of N,N-dimethylformamide and 11.4 g of N-methylpyrrolidone were placed in a three-necked flask and mixed thoroughly. 7.2 g of vacuum-dried polyetherimide was dissolved in an organic solvent under heating conditions at 60 °C and mechanically stirred for 12 h. After obtaining a uniform and transparent solution, 0.144 g of nitrogen and pyrrolidone was added thereto and mechanical stirring was continued for 2 h to obtain a polyetherimide spinning solution.
[0060] S102: Dissolve 2 g of the vacuum-dried polyurethane in 8 g of N,N-dimethylformamide, and stir under heating until it is completely dissolved to obtain a polyurethane spinning solution.
[0061] S103: Two spinning solutions were extracted separately using multiple 5 ml syringes, wherein the volume ratio of polyetherimide spinning solution to polyurethane spinning solution was 3:1. Electrospinning was performed using a multi-nozzle blending process. The spinning parameters were set as a voltage of 25 kV, a roller receiving speed of 25 r / min, a syringe propulsion speed of 0.1 mm / min, and an ambient temperature of 25 °C. The ambient humidity was 55%. It is worth noting that spinning can only begin after the temperature and humidity in the spinning machine have all reached the set values. After spinning for 6 h, the obtained fiber sponge was placed stably in an oven and heat treated at 60 °C for 1 h to obtain an A1-polyetherimide / polyurethane fiber sponge.
[0062] Example 2
[0063] This embodiment provides a method for preparing A2-polyetherimide / polyurethane fiber sponge, which specifically includes:
[0064] S201: 11.4 g of N,N-dimethylformamide and 11.4 g of N-methylpyrrolidone were placed in a three-necked flask and mixed thoroughly. 7.2 g of vacuum-dried polyetherimide was dissolved in an organic solvent under heating conditions at 60 °C and mechanically stirred for 12 h. After obtaining a uniform and transparent solution, 0.144 g of nitrogen and pyridine was added thereto and mechanical stirring was continued for 2 h to obtain a polyetherimide spinning solution.
[0065] S202: Dissolve 2 g of the vacuum-dried polyurethane in 8 g of N,N-dimethylformamide, and stir under heating until it is completely dissolved to obtain a polyurethane spinning solution.
[0066] S203: Two spinning solutions were extracted separately using multiple 5 ml syringes, wherein the volume ratio of polyetherimide spinning solution to polyurethane spinning solution was 2:1. Electrospinning was performed using a multi-nozzle blending process. The spinning parameters were set as a voltage of 25 kV, a roller receiving speed of 25 r / min, a syringe propulsion speed of 0.1 mm / min, and an ambient temperature of 25 °C. The ambient humidity was 55%. It is worth noting that spinning can only begin after the temperature and humidity in the spinning machine have all reached the set values. After spinning for 6 h, the obtained fiber sponge was stably placed in an oven and heat treated at 60 °C for 1 h to obtain an A2-polyetherimide / polyurethane fiber sponge.
[0067] Example 3
[0068] This embodiment provides a method for preparing A3-polyetherimide / polyurethane fiber sponge, which specifically includes:
[0069] S301: 11.4 g of N,N-dimethylformamide and 11.4 g of N-methylpyrrolidone were placed in a three-necked flask and mixed thoroughly. 7.2 g of vacuum-dried polyetherimide was dissolved in an organic solvent under heating conditions at 60 °C and mechanically stirred for 12 h. After obtaining a uniform and transparent solution, 0.144 g of nitrogen and pyrrolidone was added thereto and mechanical stirring was continued for 2 h to obtain a polyetherimide spinning solution.
[0070] S302: Dissolve 2 g of the vacuum-dried polyurethane in 8 g of N,N-dimethylformamide, and stir under heating until it is completely dissolved to obtain a polyurethane spinning solution.
[0071] S303: Two spinning solutions were extracted separately using multiple 5 ml syringes, where the volume ratio of polyetherimide spinning solution to polyurethane spinning solution was 5:3. Electrospinning was performed using a multi-nozzle blending process. The spinning parameters were set as a voltage of 25 kV, a roller receiving speed of 25 r / min, a syringe propulsion speed of 0.1 mm / min, and an ambient temperature of 25 °C. The ambient humidity was 55%. It is worth noting that spinning can only begin after the temperature and humidity in the spinning machine have all reached the set values. After spinning for 6 h, the obtained fiber sponge was stably placed in an oven and heat treated at 60 °C for 1 h to obtain an A3-polyetherimide / polyurethane fiber sponge.
[0072] Example 4
[0073] This embodiment provides a method for preparing A4-polyetherimide / polyurethane fiber sponge, which specifically includes:
[0074] S401: 11.4 g of N,N-dimethylformamide and 11.4 g of N-methylpyrrolidone were placed in a three-necked flask and mixed thoroughly. 7.2 g of vacuum-dried polyetherimide was dissolved in an organic solvent under heating conditions at 60 °C and mechanically stirred for 12 h. After obtaining a uniform and transparent solution, 0.144 g of nitrogen and pyrrolidone was added thereto and mechanical stirring was continued for 2 h to obtain a polyetherimide spinning solution.
[0075] S402: Dissolve 2 g of the vacuum-dried polyurethane in 8 g of N,N-dimethylformamide, and stir under heating until it is completely dissolved to obtain a polyurethane spinning solution.
[0076] S403: Two spinning solutions were extracted separately using multiple 5 ml syringes, where the volume ratio of polyetherimide spinning solution to polyurethane spinning solution was 3:2. Electrospinning was performed using a multi-nozzle blending process. The spinning parameters were set to a voltage of 25 kV, a roller receiving speed of 25 r / min, a syringe propulsion speed of 0.1 mm / min, and an ambient temperature of 25 °C. The ambient humidity was 55%. It is worth noting that spinning can only begin after the temperature and humidity in the spinning machine have all reached the set values. After spinning for 6 h, the obtained fiber sponge was stably placed in an oven and heat treated at 60 °C for 1 h to obtain the A4-polyetherimide / polyurethane fiber sponge.
[0077] Example 5
[0078] The component ratio, preparation operation and process parameters of the A5-polyetherimide / polyurethane fiber sponge prepared in this embodiment are basically the same as those in Example 1, except that the volume ratio of the polyetherimide spinning solution and the polyurethane spinning solution in this embodiment is 1:1, and the A5-polyetherimide / polyurethane fiber sponge is prepared.
[0079] Example 6
[0080] The component ratio, preparation operation and process parameters of the A6-polyetherimide / polyurethane fiber sponge prepared in this embodiment are basically the same as those in Example 1, except that the volume ratio of the polyetherimide spinning solution to the polyurethane spinning solution in this embodiment is 3:1, the spinning voltage is 20 kV, and the A6-polyetherimide / polyurethane fiber sponge is prepared.
[0081] Example 7
[0082] The component ratio, preparation operation and process parameters of the A7-polyetherimide / polyurethane fiber sponge prepared in this embodiment are basically the same as those in Example 1, except that the volume ratio of the polyetherimide spinning solution and the polyurethane spinning solution in this embodiment is 3:1, the spinning voltage is 30 kV, and the A7-polyetherimide / polyurethane fiber sponge is prepared.
[0083] At the same time, in order to verify the comprehensive performance of the fiber sponge prepared in the above examples, the present application provides the following comparative examples for detailed description.
[0084] Comparative Example 1
[0085] The component ratio, preparation operation and process parameters of the B1-fiber sponge prepared in this comparative example are basically the same as those in Example 1, except that the volume ratio of the polyetherimide spinning solution to the polyurethane spinning solution in this comparative example is 4:1, and the B1-fiber sponge is prepared.
[0086] Comparative Example 2
[0087] The component ratio, preparation operation and process parameters of the B2-fiber membrane prepared in this comparative example are basically the same as those in Example 1, except that the volume ratio of polyetherimide spinning solution to polyurethane spinning solution in this comparative example is 1:2, and a B2-fiber membrane is prepared.
[0088] Comparative Example 3
[0089] The component ratio, preparation operation and process parameters of the B3-fiber sponge prepared in this comparative example are basically the same as those in Example 1, except that the spinning voltage in this comparative example is 15 kV, and the B3-fiber sponge is prepared.
[0090] Comparative Example 4
[0091] The component ratio, preparation operation and process parameters of the B4-fiber sponge prepared in this comparative example are basically the same as those in Example 1, except that the spinning voltage in this comparative example is 35 kV, and the B4-fiber sponge is prepared.
[0092] Comparative Example 5
[0093] The component ratio, preparation operation and process parameters of the B5-fiber sponge prepared in this comparative example are basically the same as those in Example 1, except that no polyurethane spinning solution is added in this comparative example, that is, only polyetherimide spinning solution is used for electrospinning to prepare the B5-fiber sponge.
[0094] Comparative Example 6
[0095] The component ratio, preparation operation and process parameters of the B6-fiber membrane prepared in this comparative example are basically the same as those in Example 1, except that no polyetherimide spinning solution is added in this comparative example, that is, only polyurethane spinning solution is used for electrospinning to prepare the B6-fiber membrane.
[0096] In order to verify the morphological characteristics of the fiber sponge prepared in the example, the prepared fiber sponge was subjected to SEM test.
[0097] according to Figure 1 It can be seen that a) is a physical picture of polyurethane spinning solution; b) is a physical picture of polyetherimide spinning solution; the spinning solution is uniform and transparent, ensuring that continuous and uniform fibers are produced during the electrospinning process; c) is a physical picture of A1-polyetherimide / polyurethane fiber sponge, and the fiber sponge presents a three-dimensional fluffy fiber network.
[0098] according to Figure 2 It can be seen that this is the SEM image of A1-polyetherimide / polyurethane fiber sponge. It can be clearly found from the figure that the nanofibers and micron fibers enhance the interfacial bonding force through fiberization between the fibers, and the cross-linking agent can further enhance the cross-linking between the fibers and maintain good mechanical properties.
[0099] In order to verify the comprehensive performance of the fiber sponge prepared in the example, the prepared fiber sponge was subjected to a flame retardancy test, a heat insulation test and a compression test.
[0100] Flame retardant performance test: The fiber sponge prepared in the example is directly placed on a flame for testing.
[0101] Thermal insulation performance test: Since the fiber membranes obtained in Comparative Examples 2 and 6 were fiber films, no compression test was performed on them. The fiber sponges obtained in Examples 1-7 and Comparative Examples 1, 3, 4 and 5 were cut into rectangular blocks of uniform size, placed on a hot plate at a temperature of 130°C, and infrared thermal imaging photos were taken after heating for 5 minutes.
[0102] Compression performance test: Tested in accordance with GB / T 20467-2006 standard.
[0103] according to Figure 3 It can be seen that Examples 1-7 of the present application and Comparative Examples 1, 3 and 4 are all flame retardant, and the samples no longer burn after the flame is removed. In Comparative Example 2, the fiber film is no longer flame retardant because the content of the non-flame retardant polyurethane is too high.
[0104] The temperature of the fiber sponge after insulation prepared in the examples and comparative examples of the present application is shown in Tables 1 and Figure 4 As shown:
[0105] Table 1 Comprehensive performance test results of fiber sponge
[0106]
[0107] According to the test results in Table 1, the A1-polyetherimide / polyurethane fiber sponge prepared in Example 1 has the best comprehensive performance.
[0108] According to Examples 1-5, the thermal insulation performance of the polyetherimide / polyurethane fiber sponge gradually increases with the increase of the polyetherimide ratio, which is attributed to the excellent low thermal conductivity of the polyetherimide itself. However, when the content of polyetherimide is too high, such as Comparative Example 1, although the fiber sponge exhibits excellent thermal insulation, its elasticity is greatly reduced. The increase in polyurethane content will reduce the elastic modulus of the fiber sponge and enhance the elasticity of the sponge. In Examples 1-5, as the polyurethane content increases, the change in the elastic modulus of the fiber sponge is not obvious. However, compared with Comparative Example 1 with a smaller polyurethane content, and Comparative Example 5 containing only polyetherimide, the elastic modulus of Examples 1-5 is significantly reduced, which also shows that the use of polyurethane greatly enhances the elasticity of the fiber sponge. However, the higher the content of polyurethane, the better. For example, in Comparative Example 2 with a high polyurethane content, or even in Comparative Example 6 containing only polyurethane, a sponge structure can no longer be formed after spinning, but a layer of fiber membrane is obtained, and there is no polyetherimide as a protective barrier on the outside, which loses the flame retardant effect and greatly reduces the thermal insulation performance. In Examples 1-5, the fiber sponge obtained in Example 1 shows the best comprehensive performance, with excellent thermal insulation performance and elasticity. When the spinning voltage changes, the diameter of the fiber will also change, which will directly affect the performance of the fiber sponge. When the spinning voltage is 20 kV, as in Example 6, compared with Example 1, the reduction in voltage increases the diameter of the fiber, which has a greater impact on micron-level polyetherimide fibers, and the voids in the fiber sponge increase, resulting in a decrease in thermal insulation performance. When the voltage is further reduced to 15 kV, as in Comparative Example 3, the voids in the fiber sponge further increase, causing a significant decrease in thermal insulation performance. When the voltage is 30 kV, as in Example 7, compared with Example 1, the number of fibers increases, and although the diameter is reduced, the uniformity is also reduced, so the thermal insulation performance is not improved, and the elasticity is also reduced. When the voltage is increased to 35 kV, as in Comparative Example 4, the voids in the fiber sponge are further reduced, but this also makes the polyetherimide skeleton smaller, so the thermal insulation performance is not improved, but the elasticity is reduced. Comprehensive analysis shows that the volume ratio of polyetherimide spinning solution to polyurethane spinning solution and the spinning voltage will have a greater impact on the performance of the fiber sponge. In practical applications, the fiber sponge with the best performance should be obtained according to demand.
[0109] Therefore, the polyetherimide / polyurethane fiber sponge provided by the present application includes: polyetherimide micron fiber and polyurethane nanofiber; the polyurethane nanofiber is filled in the polyetherimide micron fiber skeleton to form a polyetherimide / polyurethane fiber sponge with a three-dimensional cross-linked network structure. The fiber sponge prepared by the present application has excellent fiber skeleton stability, flame retardancy, heat insulation and high elasticity and other comprehensive properties, and has broad application prospects in the fields of clothing, building insulation, and protective wear.
[0110] The various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
[0111] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit the present application. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions recorded in the aforementioned embodiments may still be modified, or some or all of the technical features therein may be replaced by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the present application.
Claims
1. A polyetherimide / polyurethane fiber sponge, characterized in that: include: polyetherimide microfibers and polyurethane nanofibers; The polyurethane nanofibers are filled in a polyetherimide micron fiber skeleton to form a polyetherimide / polyurethane fiber sponge with a three-dimensional cross-linked network structure.
2. The polyetherimide / polyurethane fiber sponge according to claim 1, characterized in that: The diameter of the polyetherimide micron fiber is 1-3 μm.
3. The polyetherimide / polyurethane fiber sponge according to claim 1, characterized in that: The diameter of the polyurethane nanofibers is 100-500 nm.
4. A method for preparing the polyetherimide / polyurethane fiber sponge according to any one of claims 1 to 3, characterized in that: The preparation method comprises: Dissolving polyetherimide in a first organic solvent, adding a cross-linking agent, and obtaining a polyetherimide spinning solution; dissolving the polyurethane in a second organic solvent to obtain a polyurethane spinning solution; The polyetherimide spinning solution and the polyurethane spinning solution are subjected to a multi-nozzle blending electrostatic spinning process, and then subjected to a heat treatment to obtain the polyetherimide / polyurethane fiber sponge; Wherein, the first organic solvent and the second organic solvent are the same or different.
5. The method for preparing the polyetherimide / polyurethane fiber sponge according to claim 4, characterized in that: The cross-linking agent is one of aziridine, bismaleimide and genipin.
6. The method for preparing the polyetherimide / polyurethane fiber sponge according to claim 4, characterized in that: The solid content of the polyetherimide spinning solution is 18%-26%; The solid content of the polyurethane spinning solution is 18%-24%; The volume ratio of the polyetherimide spinning solution to the polyurethane spinning solution is (1-3):
1.
7. The method for preparing the polyetherimide / polyurethane fiber sponge according to claim 4, characterized in that: The added amount of the cross-linking agent is 1.5%-3% of the mass of the polyetherimide.
8. The method for preparing the polyetherimide / polyurethane fiber sponge according to claim 4, characterized in that: The first organic solvent is one or more of N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone; The second organic solvent is one or more of N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone.
9. The method for preparing the polyetherimide / polyurethane fiber sponge according to claim 4, characterized in that: The parameters of the multi-nozzle blending electrospinning process are: spinning voltage: 20-30 kV; spinning temperature: 25-35 °C; spinning humidity: 40%-65%; spinning time: 3-8 h; syringe advancement speed: 0.05-0.2 mm / min; syringe left and right translation: 40-120 mm; roller receiving speed: 20-50 r / min; receiving distance: 15-30 cm.
10. Use of the polyetherimide / polyurethane fiber sponge according to any one of claims 1 to 3 or the polyetherimide / polyurethane fiber sponge prepared by the preparation method according to claims 4 to 9 in the fields of clothing, building insulation, and protective wear.
Citation Information
Patent Citations
Blended fabric of polyetherimide and flame-retardant viscose
CN103361832A
Wool-like crimpy electrospun nanofiber and preparation method thereof
CN111455474A
Reusable mask filter material and preparation method thereof
CN113085306A
Polyimide heat insulation nanofiber with controllable cavity structure as well as preparation method and application of polyimide heat insulation nanofiber
CN119061510A
Method for manufacturing a polyamide nanofibre product by electrospinning; polyamide nanofibre product; a filter medium with the polyamide nanofibre product and a filter element with such a filter medium.
EP2557206A1